A BRD4 PROTAC nanodrug for glioma therapy via the intervention of tumor cells proliferation, apoptosis and M2 macrophages polarization - Tingting Yang; Yuzhu Hu; Junming Miao; Jing Chen; Jiagang Liu; Yongzhong Cheng; Xiang Gao (Elsevier, 2022)
Glioma is a primary aggressive brain tumor with high recurrence rate. The poor efficiency of chemotherapeutic drugs crossing the blood‒brain barrier (BBB) is well-known as one of the main challenges for anti-glioma therapy. Moreover, massive infiltrated tumor-associated macrophages (TAMs) in glioma further thwart the drug efficacy. Herein, a therapeutic nanosystem (SPP-ARV-825) is constructed by incorporating the BRD4-degrading proteolytic targeting chimera (PROTAC) ARV-825 into the complex micelle (SPP) composed of substance P (SP) peptide-modified poly(ethylene glycol)-poly(d,l-lactic acid)(SP-PEG-PDLLA) and methoxy poly(ethylene glycol)-poly(d,l-lactic acid) (mPEG-PDLLA, PP), which could penetrate BBB and target brain tumor. Subsequently, released drug engenders antitumor effect via attenuating cells proliferation, inducing cells apoptosis and suppressing M2 macrophages polarization through the inhibition of IRF4 promoter transcription and phosphorylation of STAT6, STAT3 and AKT. Taken together, our work demonstrates the versatile role and therapeutic efficacy of SPP-ARV-825 micelle against glioma, which may provide a novel strategy for glioma therapy in future.